Led-based schlieren mirror system. - Sahari, Barkawi (2006)

(untitled)
The present invention provides a Schlieren optical system using LED as a light source which has low power consumption and high reliability, wherein the optical system consists of a pair of parabolic mirrors arranged on opposite directions and a knifef edge to block the reflection fraction from the mirror allowing a high speed camera to capture images of air and gas flow inside a direct injection nozzle on vehicles natural gas.